Inequality and the (self-)selection of international migrants: Theory and novel evidence - Herbert Brücker; Cécily Defoort (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
This paper analyses the (self-)selection of migrants between countries which have substantial differences in the inequality of earnings and income levels. In an extended version of the Roy-model we consider migration costs, which tend to grow less than proportional with the income level. As a consequence, migrants can be favourably self-selected although the inequality of earnings is larger in the destination relative to the sending country. Based on a novel panel data set, covering migration from 143 sending countries all over the world into the 6 main receiving countries in the OECD from 1975 to 2000, we examine the factors which drive the selection bias of the migrant population empirically. The descriptive statistics indicate that migrants tend to be positively (self-)selected although the inequality in earnings is larger in the destination relative to the sending countries. Our estimation results suggest that both, a higher inequality in the distribution of earnings in the receiving and the sending country increases the skill level of the migrant population relative to that of the population in the sending countries. Moreover, the positive selection bias decreases with the income level of the sending country at a given income differential. Finally, migration barriers and distance affect the selection bias positively. – – Der Beitrag analysiert die (Selbst-)Selektion von Migranten zwischen Ländern, in denen substantielle Unterschiede bezüglich Einkommensungleichheit bestehen. In einer erweiterten Version des Roy-Modells werden Migrationskosten betrachtet, welche dazu tendieren, weniger als proportional zum Einkommensniveau zu wachsen. Die Folge ist eine positive Selbstselektion von Migranten obwohl die Einkommensungleichheit im Einwanderungsland größer ist als im Auswanderungsland. Auf der Grundlage eines neuen Paneldatensatzes, der Daten zur Migration aus 143 Auswanderungsländern in die sechs Haupteinwanderungsländer der OECD von 1975 bis 2000 enthält, werden die Faktoren der Selbstselektion von Migranten empirisch analysiert. Die positive (Selbst-)Selektion von Migranten trotz größerer Einkommensungleichheit in den Einwanderungsländern wird von der deskriptiven Statistik belegt. Die Ergebnisse deuten darauf hin, das sowohl eine größere Einkommensungleichheit im Einwanderungsland als auch im Auswanderungsland das Qualifikationsniveau der Migranten im Vergleich zur Bevölkerung des Auswanderungslands erhöht. Außerdem sinkt der positive Selektionsbias mit dem Einkommensniveau des Auswanderungslandes bei einem vorgegebenen Einkommensdifferential. Weitere Einflussfaktoren sind Migrationshemmnisse und die Entfernung zum Auswanderungsland.
Keywords: F22; 330; International migration; self-selection of migrants; inequality; human capital of migrants